Answer:
The solution of the system is { (-t. s. 0, t) : s,t ∈ R}
Step-by-step explanation:
Lets multiply the first row by (x1,x2,x3,x4) and equalize to 0
(1,0,0,1) * (x1,x2,x3,x4) = x1+x4
which is equal to 0 only when
x1+x4 = 0
x1 = -x4
Now we can replace x1 with -x4.
If we multiply the second row (0,0,1,0) with (x1,x2,x3,x4) we will obtain (0,0,1,0)*(x1,x2,x3,x4) = x3. Since we want that product to be equal to 0, then x3 = 0. If we multiply the third row of zeros with (x1,x2,x3,x4) we will obtain automatically 0.
As a consecuence, we have 2 conditions:
We call t = x4, s = x2, which can take any value. The solutions of the system is
{ (-t. s. 0, t) : s,t ∈ R}